2014
DOI: 10.3945/jn.114.199828
|View full text |Cite
|
Sign up to set email alerts
|

Early Supplementation of Phospholipids and Gangliosides Affects Brain and Cognitive Development in Neonatal Piglets

Abstract: In summary, dietary phospholipids and gangliosides improved spatial learning and affected brain growth and composition in neonatal piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 38 publications
(51 reference statements)
4
61
2
Order By: Relevance
“…Previous studies in new‐born piglets have found no difference in cognitive function and total brain volume between piglets fed with milk containing different supplements . At birth, the piglets in our study were randomised to either parenteral nutrition or parenteral nutrition in combination with small amounts of bovine colostrum, and as we previously found no difference in later outcomes according to these diets , the data were analysed according to term or preterm delivery.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies in new‐born piglets have found no difference in cognitive function and total brain volume between piglets fed with milk containing different supplements . At birth, the piglets in our study were randomised to either parenteral nutrition or parenteral nutrition in combination with small amounts of bovine colostrum, and as we previously found no difference in later outcomes according to these diets , the data were analysed according to term or preterm delivery.…”
Section: Discussionmentioning
confidence: 84%
“…Lipids have many biological roles, from roles in brain function and development (Hellhammer et al, 2010;Nagai, 2012;Liu et al, 2014), to roles in cell cycle regulation and cell signaling (Garcia-Gil et al, 2017;Ng et al, 2017). Additionally, lipids are key components of membranes.…”
Section: Lipid Imbalance and Its Impactmentioning
confidence: 99%
“…Complex milk lipids (CML), as a source of GA, have potential benefits for brain development. [19][20][21] The rate of GA accretion in the developing brain is highest in utero and in early neonatal life. 22 23 Preclinical research has shown that CML are transferred across the placenta and as such, an increased maternal intake of CML in pregnancy has been associated with increases in fetal GA levels.…”
Section: Introductionmentioning
confidence: 99%